Advertising age handbook of advertising - Lewis, Herschell Gordon, 1926- (NTC Business Books, 1999)
This book presents about: The Purpose of Advertising; Planning the Communication; Budgeting; Creative Strategy; Media; Production; Testing and Reserch...